Moderating Effects of the Low-Income Housing Tax Credit on Associations Between Race and Elevated Blood Pressure in Chicago. - Xie, Tiffany H.; Peek, Monica E.; Tabit, Corey E.; Tung, Elizabeth L. (Journal of Urban Health, 2025)
While there is growing awareness of discriminatory housing policies and their adverse impacts on health, little is known about how housing policy may promote health equity. We focused on the Low-Income Housing Tax Credit (LIHTC), the largest affordable housing program in the United States, and examined how living in neighborhoods with LIHTC housing may moderate associations between elevated blood pressure and race/ethnicity in Chicago, IL. A retrospective cohort included 15,339 adult patients at an academic medical center from 2018 to 2019. We used mixed-effects hierarchal logistic regression models to examine elevated blood pressure (diastolic blood pressure ≥ 90 mmHg or systolic blood pressure ≥ 140 mmHg) as a function of race/ethnicity, LIHTC, and race/ethnicity-LIHTC interaction effects, adjusting for patient- and neighborhood-level covariates. A majority were female (63.2%) and non-Hispanic Black (57.6%), with an average age of 50.2 years (SD 19.1). One in ten (9.9%) patients lived in a census tract with LIHTC. Overall, Black patients had 2.52 times the adjusted odds of elevated blood pressure compared to White patients (95% CI = 2.25–2.82). In models examining the moderating effects of LIHTC, the odds ratio of hypertension in Black patients vs. White patients was reduced from 2.62 to 1.52, representing a 67.9% reduction in the difference between Black and White patients. Notably, Black patients, who have been disproportionately impacted by discriminatory housing policies, were the only group found to have moderating effects associated with LIHTC. Housing policies may mitigate neighborhood effects associated with racial disparity, possibly supporting efforts to achieve health equity.